Analysis of Intellectual Capital Effect Toward Financial Performance and Growth - Sasya Sabrina (Binus Business Review, 2015)
The purpose of this research is to investigate the influence of intellectual capital of firm toward financial performance and growth. The Value Added Intellectual Coefficient (VAICTM) is used to measure intellectual capital. The indicators for VAICTM are Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). The indicators for financial performance are Current Ratio (CR), Total Assets Turnover (TATO), Return on Investment (ROI), and Return on Equity (ROE). The indicators for growth are Earnings Growth (EG) and Assets Growth (AG). This research uses data drawn from 92 publicly listed manufacturing companies in Indonesian Stock Exchange in 2010, 2011, and 2012. Partial Least Square (PLS) is used as the method of data analysis. This research uses SmartPLS 3.2.0 to analyze the data.The results show that: intellectual capital doesn’t influence financial performance and intellectual capital positively influences growth.